Analysis of A High Rise Building Frame Considering Seismic Load Using ETABS A Review - Sahu, Omprakash; Nirmal, Pradeep Kumar (International Journal of Scientific Research in Civil Engineering, 2023)
Buildings must be able to safely withstand any significant ground motions that could happen during construction or regular operation in order to be considered earthquake resistant. The impacts that ground motions have on structural reactions, however, are special. The timehistory analysis is the analytical method that is most accurate for structures that are subjected to severe ground vibrations. For this analysis, a stepwise solution is used to integrate the pushover analysis of a multi-degree-of-freedom system, or MDOF, in the time domain in order to depict the real reaction of a structure. Although it can be applied to all practical uses, this method takes time. The pushover analysis was developed because it was necessary to develop quicker techniques that would nevertheless provide a trustworthy structural assessment or design of structures subjected to seismic loading. The foundation of pushover analysis is the presumption that during a seismic event, structures vibrate primarily in the first mode or in the lower modes. As a result, the multi-degree-offreedom system is reduced to a single-degree-of-freedom system that has attributes that are predicted by the nonlinear static analysis of the multi-degree-of-freedom system, or SDOF system. The ESDOF system is then subjected to a response spectrum analysis with constantductility spectra, or damped spectra, or a nonlinear time history analysis. Through modal connections, the seismic demands for the MDOF system are converted from the ESDOF system’s computed seismic demands.